VARIATIONS IN THE BIOLOGICAL BEHAVIOR OF CALCIFYING ODONTOGENIC CYST TO CALCIFYING CYSTIC ODONTOGENIC TUMOR: A CASE REPORT - CHESHTA WALIA; RUDRA PRASAD CHATTERJEE; SANCHITA KUNDU; MOUSUMI PAL (International Journal of Pharma and Bio Sciences, 2015)
Calcifying cystic odontogenic tumor (CCOT) is a rare odontogenic lesion comprising about 2% of all odontogenic pathological changes in the jaw. Clinically presents as painless swelling of jaw, while histopathology demonstrates characteristic “Ghost” epithelial cells with a propensity to calcify. Due to its varied clinical presentation, including cystic and neoplastic forms and recurrence rates posses a great challenge to decide its course of treatment. Here, we report, a classic case of CCOT, showing an aggressive clinical course and different histopathologic presentations along with a brief review of literature.